IMPLEMENTASI METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN RUMAH BERBASIS ANDROID - Admi Syarif; Qory Aprilarita; Muhammad Rizki; Favorisen R Lumbanraja (Universitas Teknokrat Indonesia, 2020)
The process of selecting house is a difficult thing to do, because there are many alternatives offered by developers. The purpose of this research is to build an Android-based decision support system that can help selection process involving ten criteria. The criteria used in this research are house prices, building area, land area, electricity, water sources, distance from market, distance from university, number of bedrooms, number of bathrooms, and number of floors. The system built applies Simple Additive Weighting (SAW) method. SAW is one of the well-known methods and is often used for multiple attribute decision making because of its simplicity in providing alternatives during the decision making process. Based on system performance testing, the results of accuracy is 85,7%, which at this time has been categorized as very good. Based on the results of alpha testing and beta testing, it can be concluded that application has worked and meets the level of user satisfaction, with value that is categorized as very good